2019
DOI: 10.3329/akmmcj.v10i2.44128
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Admission and Outcome in a Neonatal Intensive Care Unit (NICU) of a Tertiary Care Hospital in Dhaka, Bangladesh

Abstract: Background: The neonatal period is a highly vulnerable time for an infant completing many of the  physiologic adjustments required for life outside the uterus. As a result, there are high rates of morbidity  and mortality. To reduce morbidity and mortality it is essential to know the neonatal disease pattern.  Neonatal disease pattern changes from time to time and place. Analyzing the neonatal admission pattern  helps the policy makers to make the better strategies and health care givers to serve better. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
0
1
Order By: Relevance
“…This is similar to findings in Pakistan, India, which also reported birth asphyxia as the major cause of mortality and contributed 46% and 30% of the total mortality respectively [35,36]. Most studies however reported prematurity/low birth weight as the commonest cause of death and accounted for between 35%-70% of neonatal deaths among admitted neonates [25,26,[37][38][39]. A previous study in Bangladesh however reported neonatal infection as the predominant cause of death (29%) among the admitted neonates [40].…”
Section: Mortality Rate and Causes Of Mortalitysupporting
confidence: 83%
“…This is similar to findings in Pakistan, India, which also reported birth asphyxia as the major cause of mortality and contributed 46% and 30% of the total mortality respectively [35,36]. Most studies however reported prematurity/low birth weight as the commonest cause of death and accounted for between 35%-70% of neonatal deaths among admitted neonates [25,26,[37][38][39]. A previous study in Bangladesh however reported neonatal infection as the predominant cause of death (29%) among the admitted neonates [40].…”
Section: Mortality Rate and Causes Of Mortalitysupporting
confidence: 83%
“…About 16.3% of total admissions were due to prematurity complications which accounted for the third most common cause of admissions to the NCU. This incidence is higher than that of (Shakya et al, 2014), which was 6.5%, and this finding was different from other centers where the percentages of premature babies were higher (35% to above 50%) (Demisse et al, 2017;Tajkia et al, 2019), which suggests good ante-natal care in Al-Bayda. On the other hand, the rate of birth asphyxia 3.2% was much lower than others from Misurata and Bangladesh by (Ashour et al, 2014;Hoque et al, 2013).…”
Section: Discussioncontrasting
confidence: 57%
“…The prevalence of DAMA amongst neonates in the Rivers State University Teaching Hospital of 4.8% in the present study was similar to the 4.3% reported in a previous study [8] in the same locality, Port Harcourt done more than a decade ago but higher than the 3.97%, 3.9%, 1.7%, 1.6% and 1.5% reported in Bayelsa southern Nigeria, Bangladesh, India, Saudi Arabia and Australia respectively. 10,[18][19][20][21] Much higher prevalences of 6.7%, 7.5%, 7.7%, 9.3%, 11.1% and 25.4% were documented in Abuja northern Nigeria, Edo state southern Nigeria, India, Jigawa, Gombe northern Nigeria and India respectively. 1,4,5,7,14,22 These differences could be attributed to different geographic locations, variation over time even in the same locality, socioeconomic status, ignorance, cultural factors as well as the availability of health insurance.…”
Section: Discussionmentioning
confidence: 99%